An efficient far-red emitting Ba2LaNbO6:Mn4+ nanophosphor for forensic latent fingerprint detection and horticulture lighting applications. Issue 7 (May 2020) - Pavitra, Eluri; Raju, Ganji Seeta Rama; Park, Jin Young; Hussain, Sk Khaja; Chodankar, Nilesh R.; Rao, Gattupalli Manikya; Han, Young-Kyu; Huh, Yun Suk
Abstract: Due to their unique optical properties like narrow emission bands, the applicability of fluorescent nanomaterials have recently been extended to various fields such as forensic science and urban farming. Herein, we report a novel fluorescent material of Mn 4+ ions doped Ba2 LaNbO6 (BLN:Mn 4+ ) with nanorod-like morphology for latent fingerprint detection as well as plant growth light-emitting diodes (LEDs) through a facile citric acid-assisted sol-gel route. The crystallization, elemental composition and oxidation states present in the BLN:Mn 4+ nanophosphors are confirmed by the X-ray diffraction and X-ray photoelectron spectroscopy analyses. The photoluminescence spectra reveal a promising red emission band at 685 nm wavelength region under both 351 and 510 nm excitations, which is the required far-red emission for phototropism in plants. Furthermore, the optimized BLN:0.25Mn 4+ nanophosphors exhibited all the features required for three levels of latent fingerprint detection on various nonporous surfaces under 365 nm illumination. The fluctuation of the red value on pixel profile confirms the good affinity of BLN:0.25Mn 4+ nanophosphors with the fingerprint ridges. Because of their excellent luminescent properties and brilliant performance in the latent fingerprint detection process, the synthesized BLN:Mn 4+ nanophosphors can be considered as a promising fluorescent material for the fabrication of plant growth LEDs and latent fingerprint applications.